Pengaruh terpaan konten pengajian Gus Iqdam Muhammad terhadap peningkatan literasi keislaman generasi millenial di Kabupaten Trenggalek - Putranto, Lutfi Afip; Prajawinanti, Arin (Nur Science Institute, 2024)
Introduction: Information technology in the last few decades has undergone a fairly rapid development. These developments show a change in the way humans interact using new media. YouTube has become one of the social media forms of new media. The millennial generation is a generation whose lives have not been separated from social media, but unfortunately in its use is often used only as a means of entertainment, although in fact there is a lot of useful content in it, such as Islamic content. However, content like this is generally less in demand because of its nature that tends to be serious and not entertaining. One of the youtube channels that attracted a lot of attention from users of social media is the youtube channel Gus Iqdam Officiall. Exposure messages on social media has become one of the containers for disseminating information that has the potential to enhance Islamic literacy. The aim of this research is to find out the impact of Gus iqdam Mohammad's study content on the improvement of millennial generation Islamic literacy in Trenggalek district. Data Collection Methods: This research is research that uses quantitative methods, with data collection methods, namely by distributing online questionnaires using Googleform to respondents in the 22 to 43 year old category who live in Trenggalek Regency with a sample size of 100 people. Data Analysis: The data obtained from distributing online questionnaires was then processed and analyzed with the help of the IBM SPSS V.25.0 application. Results and Discussion: The results showed that there was an effect of exposure to Gus Iqdam Muhammad's recitation content on increasing the Islamic literacy of the millennial generation in Trenggalek district. This result is indicated by the calculated t value of 9.950 which is greater than the t table value of 1.984 and the significance value of 0.000 is smaller than 0.05 at the 5% significance level. So that Ha is accepted and H0 is rejected. The magnitude of the influence of the exposure of Gus Iqdam Muhammad's recitation content on increasing the Islamic literacy of the millennial generation in Trenggalek Regency is indicated by the R square value of 0.484 which indicates that there is an influence of 48.4% while the remaining 51.6% is due to factors not discussed in this study. Conclusion: The results showed that there was an effect of exposure to Gus Iqdam Muhammad's recitation content on increasing the Islamic literacy of the millennial generation in Trenggalek district. Through these results, it is hoped that this research can provide insight into how effective the media is in increasing Islamic literacy.